Il paesaggio dentro il museo (Lebenswelt. Aesthetics and philosophy of experience., 2014)
At the end of the nineteenth century the conception of the museum begins to change, and during the twentieth century it becomes a place not exclusively devoted to conservation. In the last few years, museums invested a lot in the atmospheric components. What is the visitor’s mood in the appreciation of the museum space? How can the aesthetics of atmospheres be an instrument for investigating the phenomenon? The paper analyzes the contribution of this approach to the museum space.